Uncommon threads: pneumopericardium complexity following liver catheter removal in pancreatic cancer - Ahmed Basuoni; Sameera Khatri; Yasir Al-Malki; Marwa Makhlouf (Exploration of Cardiology, 2024)
Pneumopericardium, the presence of air within the pericardial sac, is a rare but critical condition that can lead to severe complications such as tension pneumopericardium and cardiac tamponade, causing hemodynamic instability and necessitating immediate intervention. Various etiologies include congenital defects, post-surgical complications, infections, and trauma. Malignancies, such as advanced esophageal cancer or lung carcinoma, can also cause pneumopericardium via fistula formation. Multimodal imaging, including chest X-ray, echocardiography, and computed tomography (CT), is essential for diagnosis. This case report discusses a 65-year-old male with advanced pancreatic adenocarcinoma who developed pneumopericardium following the removal of a left lobe liver drainage catheter. Initial CT imaging revealed liver lesions suspicious for metastatic disease or abscess, leading to drainage procedures. Following the removal of the drainage tube, the patient experienced respiratory distress and hypotension, and computed tomography pulmonary angiogram (CTPA) revealed pneumopericardium, likely due to a fistula formed between the abscess and pericardium. Despite no echocardiographic signs of tamponade, the patient’s persistent hypotension warranted CT-guided pericardiocentesis, resulting in gradual blood pressure improvement. This case highlights the intricate interplay between malignancy, infection, and procedural complications in developing pneumopericardium. It emphasizes the need for a multidisciplinary approach and the importance of considering both the quantity and rate of air accumulation when assessing the risk of hemodynamic compromise. The patient’s hemodynamic instability and subsequent improvement following pericardiocentesis underscore the critical role of timely intervention in managing this condition.